A multi-target protective effect of Danggui-Shaoyao-San on the vascular endothelium of atherosclerotic mice - Yuemeng Sun; Yushan Gao; Lu Zhou; Yixing Lu; Yulin Zong; Haoyu Zhu; Yang Tang; Fengjie Zheng; Yan Sun; Yuhang Li (BMC, 2023)
Abstract Background Atherosclerosis (AS) is a chronic disease characterized by abnormal blood lipid metabolism, inflammation and vascular endothelial injury. Vascular endothelial injury is the initial stage during the occurrence of AS. However, the function and mechanism of anti-AS are not well characterized. Danggui-Shaoyao-San (DGSY) is a classic Traditional Chinese Medicine (TCM) prescription for the treatment of gynecological diseases, and has been widely used in the treatment of AS in recent years. Methods ApoE−/− atherosclerosis male mice were established by feeding with high-fat diet, and then randomly divided into three groups: Atherosclerosis group (AS), Danggui-Shaoyao-San group (DGSY), and Atorvastatin calcium group (X). The mice were administered with the drugs for 16 weeks. Pathological changes in aortic vessels were examined by staining with Oil red O, Masson and hematoxylin-eosin. In addition, blood lipids were analyzed. The level of IL-6 and IL-8 in aortic vessels were detected by ELISA and the expression of ICAM-1 and VCAM-1 in the aortic vascular endothelium were measured by Immunohistochemical. The mRNA expression of interα5β1/c-Abl/YAP in the aortic vessels were measured by Real-time quantitative PCR and location of expression was assessed by immunofluorescence. Results DGSY can significantly reduce the content of TC,TG and LDL-C and increase the level of HDL-C in the serum, reduce the plaque area and inhibit the concentration of IL-6 and IL-8, down-regulate the expression of IVAM-1,VCAM-1 and interα5β1/ c-Abl/YAP in the aortic vessels. Conclusions Collectively, DGSY can alleviate vascular endothelium damage and delay the occurrence of AS, and the underlying mechanism may be related to the multi-target protective of DGSY.